The relationship between athletic mental energy and eating behaviors in tennis players - Ilhan, Aydin (Progress in Nutrition, 2021)
Study Objectives: The study aim of this study was to investigation of the relationship between athletic mental energy and eating habits in tennis players. Methods: 355 tennis players with a mean age of 20.93 ± 4.26 and a mean sports age of 9.50 ± 2.25 years participated in the study. The Athletic Mental Energy Scale (AMES) and Eating Habits Questionnaire (EHQ) were used in the study. AMES was developed by Lu et al. (2018) and adapted to Turkish language by Yıldız et al. (2020). AMES consists of 18 items and 6 sub-dimensions and was evaluated as 6 likert-type. First and second level confirmatory factor analyses were examined for construct validity of the scale. Internal consistency coefficients were calculated for reliability assessment, and item-total test correlations were also examined to determine internal consistency. The Eating Habits Questionnaire, adapted by Mahmoud and Taha (2017), was a likert-type scale with five options. SPSS 21.0 package program was used for the analysis of the data obtained. Independent Samples T-test for binary comparisons and One-Way ANOVA for multiple comparisons were applied for research analysis. The analysis of the data was evaluated at a 95% confidence interval and a significance level of p <0.05. Results: it was determined that there was a significant difference in confidence and calmness sub-dimensions of male tennis players in AMES according to gender, but no significant difference was found in eating habits. It was determined that 330 (98.5%) of the tennis athletes had a neutral nutritional habit. No significant difference was found in AMES and eating habits according to the number of training days. Conclusion: we can say that there was a positive relationship between eating planning and non-fatigue energy in tennis players.